Cuatro especies y una variedad del género Astrosphaeriella (Dothideales, Melanommataceae) de México - San Martin, Felipe Eduardo; Antonio Lavin, Pablo (Instituto de Ecología, A.C., 1999)
Astrosphaeriella stellata (Pat.) Sacc., A. stellata var. palmicola var. nov., A. tornata (Berk. et M. A. Curtis) D. Hawksw. et Boise, A. trochus (Penzig et Sacc.) D. Hawksw., and A. vaginata sp. nov., are described and illustrated. An artificial key is provided for the considered taxa.